2009
DOI: 10.1098/rspa.2009.0010
|View full text |Cite
|
Sign up to set email alerts
|

Elastic waves guided by a welded joint in a plate

Abstract: The inspection of large areas of complex structures is a growing interest for industry. An experimental observation on a large welded plate found that the weld can concentrate and guide the energy of a guided wave travelling along the direction of the weld. This is attractive for non-destructive evaluation (NDE) since it offers the potential to quickly inspect for defects such as cracking or corrosion along long lengths of welds. In this paper, a twodimensional semi-analytical finite-element (SAFE) method is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 18 publications
2
63
0
Order By: Relevance
“…This was found first by observation of a compression-like mode [13], which is dispersive, partially-trapped at low frequencies, and perfectly-trapped at high frequencies. This geometry was then investigated by model and further experiments, showing the existence of both the compression-like mode and a perfectly-trapped shear-like mode with very little dispersion [14,15]. The shear-like mode is slower than any other mode at all frequencies, and so does not leak any energy into the adjacent plates.…”
Section: Introductionmentioning
confidence: 99%
“…This was found first by observation of a compression-like mode [13], which is dispersive, partially-trapped at low frequencies, and perfectly-trapped at high frequencies. This geometry was then investigated by model and further experiments, showing the existence of both the compression-like mode and a perfectly-trapped shear-like mode with very little dispersion [14,15]. The shear-like mode is slower than any other mode at all frequencies, and so does not leak any energy into the adjacent plates.…”
Section: Introductionmentioning
confidence: 99%
“…Such an effect is closely related to feature-guided wave phenomena noted in the literature in recent years. 3,7,8 Also an interesting observation is that pipe eccentricity does not seem to affect the T(0,1) mode as strongly, and its modal structure and nondispersive nature are very similar to the circular pipe even in cases of high ovalness. This paper is organized as follows.…”
Section: Introductionmentioning
confidence: 94%
“…3,7,8 Recent analytical studies (Postnova and Craster 11,12 ) have shown that curvature effects in waveguides are mathematically equivalent to local thinning. Again drawing upon the work of Postnova and Craster, 11,12 we find that for longitudinal modes, trapping is only possible for local thinning for Poisson ratio in the range of metals.…”
Section: Understanding the Physics Of Mode Focusing Based On Literaturementioning
confidence: 99%
“…The SAFE method is popular for studying properties of guided waves along waveguides with arbitrary cross-section, such as railway lines [48], beams [49,50], welded [51] or stiffened plates [52], etc. It uses FEs to represent the cross-section of the waveguide, plus a harmonic description along the propagation direction, thus limiting the FE model to two dimensions.…”
Section: The Semi-analytical Finite-element Models For Validation Of mentioning
confidence: 99%